IMPLEMENTASI PENDIDIKAN KARAKTER DENGAN HASIL PENCAPAIAN HAFALAN ALQUR’AN DIRUMAH TAHFIDZ ALQUR’AN RABBANI - Pohan, Siti Maharani; Zuliana, Zuliana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
In the implementation of character education, Ustadz and Ustadzah who teach at the Rabbani Al-Qur’an Tahfidz house play an important role in improving the quality of the character of students as memorizers of the Qur’an, the purpose of this study is to find out how the implementation of character education with the achievement of students’ memorization of the Qur’an, supoting factors, and inhibiting factors in the implementation in achieving memorization of the Qur’an. This form research used in the journal article is qualitative research using a descriptive approach. The subject of this reasrch are the Tahfidz House foundation, ustadz and ustadzah who teach,and students. Data collection techniques in this study used interviews, observation, and documentation. Rhe result of this study indicate that the implementation of character education is very important in the achievement of studens’ memorization of the Qur’an . this study also shows that the implementation of character education in the achievement pf memorization of students is the Rabbani Al-Qur’an tahfidz house as a whole has gone well, as for its mplementation includes (1) tahfidz method, (2) takrir method, (3) tartil method, then the supporting and inhibiting factors for memorizing the Koran are (1) social environmental factors, (2) Al-Qur'an provided by the tahfidz house, (3) availability of dormitories for memorization, (4) the existence of tahfidz teachers, inhibiting factors, namely: (1) the lazy nature arising from the students, (2) less.